2017
DOI: 10.3892/etm.2017.5432
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of local hypothermia in a computer‑controlled compression model in minipig: Correlation of tissue sparing along the rostro‑caudal axis with neurological outcome

Abstract: This study investigated the neuroprotective efficacy of local hypothermia in a minipig model of spinal cord injury (SCI) induced by a computer-controlled impactor device. The tissue integrity observed at the injury epicenter, and up to 3 cm cranially and caudally from the lesion site correlated with motor function. A computer-controlled device produced contusion lesions at L3 level with two different degrees of tissue sparing, depending upon pre-set impact parameters (8N- and 15N-force impact). Hypothermia wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Wang et al [ 48 ] have reported that neurofilament gene transcriptional regulation is crucial for neurofilament expression predominantly in axonal regeneration. We have also recently pointed out the role of neurofilaments in modulating spinal microcircuits leading to a better functional outcome [ 49 ]. Although the Olig2 transcription factor, an essential regulator of oligodendrocyte development, has been seen to improve locomotor recovery and enhance myelination in a rat contusive spinal cord injury model [ 50 ], we did not see any neuroprotective effect of the ATR treatment in Olig2 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 48 ] have reported that neurofilament gene transcriptional regulation is crucial for neurofilament expression predominantly in axonal regeneration. We have also recently pointed out the role of neurofilaments in modulating spinal microcircuits leading to a better functional outcome [ 49 ]. Although the Olig2 transcription factor, an essential regulator of oligodendrocyte development, has been seen to improve locomotor recovery and enhance myelination in a rat contusive spinal cord injury model [ 50 ], we did not see any neuroprotective effect of the ATR treatment in Olig2 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia increases adenosine triphosphate (ATP) stores, helps to maintain the normal transmembrane ion and neurotransmitter gradients, preserve the BSCB (blood-spinal cord barrier), ameliorate the local oedema, suppress axonal swelling and development of gliosis, reduce oxidative stress, inflammation, and mitochondrial membrane permeabilization which is the point-of-no-return in apoptosis (Alkabie and Boileau 2016). Interesting results of experimental studies in minipigs showed that local SC cooling by 4 °C solutions administered by a peristaltic pump to the perfusion chamber placed through laminectomy at the epicentre of spinal trauma, starting 30 min after injury and maintained for 5 h, is safe, allows to maintain stable body temperature, does not create adverse reactions, does not need a special rewarming protocol, and improves both, clinical outcome and histopathological features of SC samples (Gedrova et al 2018). However, the decelerated function of enzymes can slow the metabolism of medicaments.…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
“…In the present study, we wanted to test the protective effect of local hypothermia after precisely-controlled SCI model in minipigs ( 56 , 57 ) representing a preclinical model which mimics human patients more closely than the widely-used rodent models. In a series of experiments, we modified i) the cooling approach (durotomy vs. intact dura mater), ii) the kind of cooling solutions (saline, medium or enriched medium), and iii) the degree of hypothermia (15 or 24°C just above the SCI).…”
Section: Introductionmentioning
confidence: 99%